Large floating thrombus in the inferior vena cava - Hussein, Rayan; Alrabyee, Khalid; Karrar, Abdulrazak; Hamdan, Nourah; Al-Hudaithi, Mogbil; Al Shammeri, Owayed (International Journal of Health Sciences, 2019)
A 32-year-old female presented to the emergency room with severe right loin pain. Abdominal color Doppler ultrasound (CDUS) observed a large thrombus in the inferior vena cava (IVC). Computed tomography with contrast described a large floating thrombus in the IVC with no visible wall attachment. Emergency transjugular suprarenal IVC filter was inserted and overnight infusion thrombolysis over 24 h. The patient started to show constitutional symptoms of pyelonephritis such as high-grade fever and pyuria post-thrombolysis. Immediate empiric antibiotic coverage was started. Overnight infusion thrombolysis resulted in resolution of the floating thrombus and the IVC filter was removed in the next day. Urine culture grew Escherichia coli and tailored antibiotic therapy was completed. Three months CDUS confirmed complete resolution of the IVC thrombosis.